Rupture of a ventricular abscess after mitral valve replacement. Issue 3 (March 1992) - Weale, A E; Hutter, J; Collins, C M
Abstract : A 65 year old man presented with bacterial endocarditis of the mitral valve. Immediately after mitral valve replacement a valve ring abscess ruptured. Early surgery should be performed when an intramyocardial abscess is suspected.